2013
DOI: 10.1108/ijlma-10-2011-0012
|View full text |Cite
|
Sign up to set email alerts
|

A critique of corporate governance in China

Abstract: PurposeThis paper aims to offer a critique of corporate governance in China.Design/methodology/approachThe critique is based upon a literature review and secondary data sources.FindingsThe Chinese Government has made efforts to strengthen the effectiveness of corporate governance in state‐owned enterprises. However, existing research shows that some governance mechanisms that are effective in Western countries have no significant or negative impacts on firm performance in China. An apparent reason for this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 59 publications
0
31
0
1
Order By: Relevance
“…Shares held by state-owned shareholders exceed other shares held by other shareholders (individuals and NSOEs) in Chinese companies. Guo et al (2013) reported that by end of September 2006, largest shareholders who held 56% of shares were state shares controlled by Chinese government and other state asset management companies.…”
Section: China As a Unique Market Settingmentioning
confidence: 99%
“…Shares held by state-owned shareholders exceed other shares held by other shareholders (individuals and NSOEs) in Chinese companies. Guo et al (2013) reported that by end of September 2006, largest shareholders who held 56% of shares were state shares controlled by Chinese government and other state asset management companies.…”
Section: China As a Unique Market Settingmentioning
confidence: 99%
“…Chinese companies are highly concentrated in term of ownership concentration. A single largest owner holds about 36% of an average company share, while 52% shares are held by five biggest owners (Guo et al 2013). This higher ownership concentration will affect the decision making process regarding Chinese firms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the situation becomes more complex while considering the fact of SOEs and NSOEs. Guo et al (2013) reported that by end of September 2006, largest shareholders who held 56% of shares were state shares controlled by Chinese government and other state asset management companies. Until 1998, the largest Chinese banks (most of them were state owned) were advised not to give credit to Chinese private companies.…”
Section: Introductionmentioning
confidence: 99%
“…Even Germany has initiated a process of transformation in this direction (Yeoh, 2007). Nevertheless, there are exceptions, such as China, where the mechanisms implemented in the West have no impact on the state-run companies of this Asian country (Guo et al, 2013). Another problem that has been identified is the excessive concentration of power in the hands of majority shareholders, to the detriment of minority shareholders (Agyemang & Castellini, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are in violation of the guidelines of the country's Ministry of Corporate Affairs. Guo et al (2013) study the corporate governance of state-owned companies in China, finding that mechanisms implemented in the West have no impact in this Asian country due to the strong relationship between the companies and the State. For his part, Payne (2016) emphasizes that although clear distinctions remain, there is a growing similarity between American and European corporate governance.…”
Section: Codes Of Corporate Governancementioning
confidence: 99%